Application of hair HPG axis hormone levels before onset in predicting the risk of stroke - Yang, Jiao; Li, Shuhan; Li, Xuan; Wang, Tiantian; Deng, Huihua; Jia, Yuanyuan; Meng, Dianhuai (Frontiers in Neurology, 2025)
BackgroundThere have been many studies on the relationship between sex hormones and stress, mood, blood pressure, etc., but its impact on the incidence of stroke remains unknown.ObjectiveTo investigate the expression levels of hypothalamic–pituitary-gonadal (HPG) axis related hormones such as testosterone (T) and progesterone (P) in hair before stroke and their effects on the risk of stroke.Methods48 patients with stroke were recruited from November 2022 to May 2023 as the observation group and 35 healthy subjects were recruited as the control group. There was no obvious difference in age, gender and BMI between the two groups (p > 0.05). T and P levels in hair were tested by LC-MS/MS, and the correlation with the risk of stroke was analyzed.ResultsThe T and P levels of hair before the onset of stroke in the observation group were significantly lower than those in the control group (p < 0.01). The T level of men’s hair before the onset of stroke in the observation group was significantly lower than those in the control group (p < 0.05). The T and P levels of women’s hair before the onset of stroke in the observation group were significantly lower than those in the control group (p < 0.01). The results of ROC curve showed that the cut-off value of T level in men’s hair before the onset of stroke was 4.35 pg/mg, the AUC was 0.690 (0.545, 0.835), the sensitivity was 62.50%, and the specificity was 82.61%. The cut-off value of T level in women’s hair before the onset of stroke was 5.00 pg/mg, the AUC was 0.818 (0.658, 0.978), the sensitivity was 75.00%, and the specificity was 83.33%. The cut-off value of P level in women’s hair before the onset of stroke was 8.00 pg/mg, the AUC was 0.891 (0.754, 1.000), the sensitivity was 81.25%, and the specificity was 100.00%.ConclusionThis preliminary report is the first to suggest that HPG axis hormones such as T and P in hair could have predictive value in screening for stroke risk.